Pemberdayaan Perempuan Rawan Sosial Ekonomi Melalui Industri Ekonomi Kreatif “Sambar” di Desa Jimbar, Kecamatan Pracimantoro - Lestari, Anis Dwi; Nisa, Azka Zahrotun; Ma’rufah, Aprilia Nurul; Setyowati, Eka Yuni; Saputri, Enriawati Ika Dyah; Utami, Fitria Nur; Khasanah, Widia Nur; Susanti, Aprilia; Purbondari, Elysa Wahyu; Wibowo, Galih Aprilia; Demartoto, Argyo (Universitas Muhammadiyah Sidoarjo, 2022)
The empowerment program aims to create a more independent society, especially women who are socio-economically vulnerable. Various obstacles such as limited education, skills, and the burden of household responsibilities that are delegated to women make it difficult to work in the public sphere. Seeing the current conditions, it is important for women to be empowered in the economic sector. This research was conducted in Jimbar Village, Pracimantoro, Wonogiri, Central Java with qualitative methods and a case study approach. Wonogiri Regency, especially Jimbar Village has abundant chili farming results. However, there are times when a fertile chili brings arid. Post-harvest constraints that often coincide with declining selling prices make chili farmers lose money. For these losses, innovation was born as a solution to overcome losses by exploiting the potential of chilies to be processed products for eating lexat, the typical chili sauce of Jimbar Village. Collaborating with the Jimbar Village PKK group, where a total of 96 cadres are spread across seven hamlets. The results showed that there was support from village officials to empower women, so that the confidence and enthusiasm of PKK women in Jimbar Village arose to establish an economic business. Through the empowerment program in Jimbar Village, several activities were carried out such as training in economic business skills, especially making durable Jimbar chili sauce by applying cleanliness, publication training using social media ranging from Tiktok, Instagram, and online shops such as Shopee.